Vocational training in sport and recreation micro-enterprises as an education project - V. Komleva, Svetlana; V. Andryukhina, Tatyana; V. Ketrish, Evgeniya; V. Tretyakova, Nataliya; P. Korotkikh, Irina; S. Okrimenk, Tatyana (International Journal of Engineering and Technology, 2018)
This study appears urgent due to the need to create new jobs in the sport and recreation sector and to update the existing approach to vocational training in a micro-enterprise. This paper proposes an education project as a form of vocational training in such conditions. The authors aim to comprehend the current issues of pedagogical design for the transfer of experience within a micro-enterprise of the sport and recreation sector and to determine the conditions for effective educational interaction of micro-enterprise employees. This problem is addressed with a combination of the systematic approach and activity-based learning. This makes it possible to present the process of pedagogical design of vocational training in the conditions of a micro-enterprise as systematic activity of individuals in developing the professional competencies of a sport and recreation worker. The authors used theoretical and empirical methods. The theoretical methods were analysis of the psychological, pedagogical, sociological, scientific-methodological and specialized literature on the studied problem; the systematic approach to the definition of the problem and the formation of the research terminology; and analysis of the legal acts. The empirical methods were pedagogical observation; study and generalization of pedagogical experience; pedagogical design; questioning; conversation; interview; performance analysis; and expert evaluation method and integration of expert opinions.Â Â